Analyzing the relationship of strengths to personality preferences and vocational interests utilizing Clifton StrengthsFinder, Myers-Briggs Type Indicator, and Strong Interest Inventory - Schenck, Paulette M., author; Feller, Rich, advisor (Colorado State University. Libraries, 2009)
Throughout the history of vocational psychology, career counselors have constantly searched for, devised, and implemented practices and techniques to best prepare clients for the world of work. The purpose of this study was to explore the relationship between strengths to personality preference and vocational interests utilizing the Myers-Briggs Type Indicator (CPP, 2003), Strong Interest Inventory (CPP, 2005), and the Clifton StrengthsFinder (Gallop, 2005) with 164 graduate students from two academic programs in an effort to expand career counseling knowledge and practice. Multiple interactions were observed between strengths and personality preferences. All (100%) of those with Communication and Woo as one of their top five strengths were Extravert. This same pattern occurred between Analytical and Significance with Sensing, Analytical with Thinking, and Discipline and Significance with Judging. Traits appearing with strengths 90 to 99% of the time included Extravert with Activator, Feeling with Empathy, and Judging with Consistency. One strength was totally (100%) associated with a mental function (Analytical and Sensing-Thinking); however, several had no association. This same pattern of connections and non-connections occurred between other strengths and personality types. In comparing strengths by top ten percent occurrence (90-100%) with the top clarity category, significant differences occurred. For example, while 100% of certain traits were paired with particular strengths by occurrence, these traits did not always have very clear clarity. This disparity suggests the relationship between personality traits and strengths may be more complex than just occurrence or clarity alone would indicate. The relationship between strengths and vocational interests was less defined. With few exceptions, all vocational interest-strength combination means were within one standard deviation. This lack of discernible interaction between vocational interests and strengths perhaps suggests that strengths can be applied across vocational endeavors, rather than being attracted to particular activities; supporting the notion that strengths are not field specific and can be applied across multiple life roles. Differences were further observed between two additional variables of gender and academic program. Some strengths were common between genders and academic programs but rankings often differed, while others were unique to the individual categories.
Keywords: Clifton strengthsfinder; Myers-Briggs Type Indicator; personality preferences; strengths; strong interest inventory; vocational interests; school counseling; quantitative psychology; personality traits; vocational education; psychological tests